Clinical characteristics, diagnosis, treatment, and prognosis of Atezolizumab-induced encephalitis, aseptic meningitis or meningoencephalitis - Yan, Qingzi; Hu, Yixiang; Liu, Xiang; Xia, Hong (Frontiers in Human Neuroscience, 2025)
ObjectiveImmune checkpoint inhibitors (ICIs) have revolutionized cancer treatment and expanded the range of tumor indications. However, as the usage of this medication has increased, related adverse events are increasingly being identified. Among these, Atezolizumab-induced encephalitis, aseptic meningitis, and meningoencephalitis remain poorly understood regarding clinical features. This study provides a comprehensive reference for classifying, identifying, and managing Atezolizumab-associated neurological adverse events, specifically encephalitis, aseptic meningitis, and meningoencephalitis.MethodsThis study systematically collected published case reports from public databases such as PubMed, Web of Science, Wanfang Database, and CNKI Database. Two independent reviewers screened titles and abstracts and then extracted data in the included article according to the designed table and analyzed the clinical characteristics of Atezolizumab-induced encephalitis, aseptic meningitis, or meningoencephalitis.ResultsA total of 17 articles were included, with 19 patients diagnosed with encephalitis, aseptic meningitis, or meningoencephalitis after Atezolizumab treatment. The most common presenting symptoms included fever, altered consciousness, fatigue, somnolence, and seizures. Diagnosis was primarily based on cerebrospinal fluid analysis, blood tests, and imaging studies, such as computed tomography (CT) scans. Treatment strategies typically involved systemic steroids, antiviral agents, antibiotics, and anti-epileptic medications, as appropriate.ConclusionNeurological immune-related adverse events may rapidly progress and impact prognosis. Therefore, clinical practitioners should have a deep understanding of these neurological immune-related adverse events, promptly diagnose them, and provide accurate and timely treatment.